Protection of Human Rights in the Context of Combating of Counterfeiting Medicines: Theoretical and Legal Issues of International Cooperations - Filei Yurii Vladimirovich1, Davidov Pavel Grigorovich2, Dmytro Yermolenko3, Koverznieva Hanna4, Vasy (Institute of Medico-legal Publications Pvt Ltd, 2020)
The article highlights the problematic issues of implementing of the best international practices in protectionof a human and human rights, and counterfeiting medicines in the context of globalization. Every stateexists for man, for the protection of universally recognized rights and freedoms. Counterfeiting of medicalproducts and other similar crimes require attention in any country in the world.Counterfeiting is not an exception in developed countries in Europe, such as the Netherlands, Belgium,Sweden, Switzerland, Finland, Norway, Denmark, and Austria. This problem is global for, both, legal andpublic administration science. It is widespread throughout the world, and the negative effects of this crimehave severe consequences that affect people’s lives and health.